INGESTION OF CARIOGENIC FOODS, ORAL HEALTH AND ORAL MICROBIOTA OF UNIVERSITY STUDENTS - Gabriela Silva Cruz; Davide Carlos Joaquim; Francisco Cezanildo Silva Benedito; Ana Karine Rocha de Melo Leite; Raquel Oliveira dos Santos Fontenelle; Erika Helena Salles de Brito; Ana Caroline Rocha de Melo Leite (Sociedade Brasileira de Enfermagem em Feridas e Estética, 2022)
Objective: To evaluate the relation between the ingestion of cariogenic foods by university students from African countries, the presence of dental caries and Candida spp. and the value of salivary pH. Methods: Transversal and analytic study, carried out at a Brazilian university. The ingestion of cariogenic foods was evaluated through a questionnaire and the rate of decayed, missing and filled teeth was determined (DMFT Index). To quantify the pH, an indicator strip was immersed in collected saliva. Identification of Candida spp. was carried out through a culture of the sample in CHROMagar Candida™. To analyze the data, we applied Kruskal-Wallis, Mann-Whitney and Qui-Square tests, considering a value of p < 0.05. Results: Out of 133 participants, 57.89% were Guinean, 20.30% had Candida spp. in their oral cavity and the majority ingested cariogenic foods and had a salivary pH of 7. The highest average in DMFT Index was observed among those who ingested dessert, chocolate and juice boxes. As for the ingestion of cariogenic foods among students with Candida spp. in their oral cavity, 44.44% and 33.33% ingested sweetened cookies and dessert once a week, respectively. The majority of participants who ingested dessert, chocolate, juice boxes and chocolate milk, regardless of frequency of ingestion, showed a pH of 7. Conclusion: In general, students, despite ingesting cariogenic foods, even with a weekly frequency, had low DMFT Index, adequate salivary pH and Candida wasn't present.